The Impact of Digital Transformation on Wage Determination: A Literature Study on the Service Industry in Indonesia - Erna Nur Faizah (CV. HEI PUBLISHING INDONESIA, 2026)
This study discusses the impact of digital transformation on wage determination in the service industry in Indonesia through a literature review approach. The development of digital technologies such as automation, artificial intelligence, digital platforms, and online-based services has changed the structure of the labor market and compensation system in Indonesia. This study aims to analyze the influence of digital transformation on wage determination, identify factors that affect wage changes, and examine the implications of digitalization on labor inequality in the service sector. The research uses the Systematic Literature Review (SLR) method by examining various national and international articles. The results show that digital transformation affects wage structures by increasing demand for high-skilled labor and reducing the need for routine and low-skilled jobs. In addition, the emergence of the gig economy and digital platform-based jobs has also created a more flexible wage system and increased income disparity between workers. Digital skills, education, technology adaptation, and productivity are the main determinants in determining wages in the service industry. This study concludes that digital transformation provides opportunities as well as challenges for the wage determination system in Indonesia, especially related to wage inequality and workforce readiness.